Identifikasi Kriteria Perancangan ‘Eks Palaguna’ di CBD Kota Bandung Berdasarkan Identitas Kota melalui Sense of Place - Paramitasari, Angela Upitya; Utami, Witanti Nur; Adrian, Aria (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
The 'Ex Palaguna ' area was the original mall in Bandung City, but has since been abandoned due to high competition. The mall was destroyed at the end of 2014. The area became a parking lot and deprived the city of a certain identity. The following research aims to re-create such urban identity as part of central Bandung. The research seeks the aspects and criteria that should be considered for 'Ex Palagun a' development as the basis for planning and design that are appropriate to its contribution to city identity and a sense of place. The method used in this research is qualitative with case study analysis. The results suggest that traditional qualities in defining ‘place’, such as form, activity, and image are highly significant to the proposed 'Ex Palaguna ' area. Keywords: ex Palaguna, mall, sense of place, city identity